Modulating embryonic signaling pathways paves the way for regeneration in wound healing - Frech, Sophie; Lichtenberger, Beate M. (Frontiers in Physiology, 2024)
Epithelial tissues, including the skin, are highly proliferative tissues with the capability to constant renewal and regeneration, a feature that is essential for survival as the skin forms a protective barrier against external insults and water loss. In adult mammalian skin, every injury will lead to a scar. The scar tissue that is produced to seal the wound efficiently is usually rigid and lacks elasticity and the skin's original resilience to external impacts, but also secondary appendages such as hair follicles and sebaceous glands. While it was long thought that hair follicles develop solely during embryogenesis, it is becoming increasingly clear that hair follicles can also regenerate within a wound. The ability of the skin to induce hair neogenesis following injury however declines with age. As fetal and neonatal skin have the remarkable capacity to heal without scarring, the recapitulation of a neonatal state has been a primary target of recent regenerative research. In this review we highlight how modulating dermal signaling or the abundance of specific fibroblast subsets could be utilized to induce de novo hair follicles within the wound bed, and thus to shift wound repair with a scar to scarless regeneration.